Changes in Marital Satisfaction across Transition to Parenthood: A Systematic Literature Review - Faradila, Riska; Pudjiati, Sri Redatin Retno (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The transition to parenthood represents a critical phase in married life that can affect various aspects of a marital relationship. Role changes, increased responsibilities, and postpartum emotional and physical stress can influence the dynamics between partners, ultimately impacting marital satisfaction. Although marital satisfaction has been widely studied, research systematically exploring the factors affecting it during the transition to parenthood remains limited. This study aims to identify the factors contributing to marital satisfaction during this transitional period. A systematic literature review (SLR) was conducted following PRISMA guidelines, with articles searched across five major databases: APA PsycArticles, PubMed, Scopus, Sage Journals, and Taylor & Francis. From 20 articles meeting the inclusion criteria, findings indicate that marital satisfaction is influenced by both individual factors (attachment, self-compassion, self-regulation, emotion, mindfulness, psychological distress, and own body satisfaction) and relational factors (perceptions of the partner, communication, interpersonal relationships, conflict resolution, sexual, and readiness for parenthood). Overall, marital satisfaction during the transition to parenthood emerges from the complex interaction between these factors. These results are expected to serve as a reference for counselors and psychologists in understanding the complexities of marital dynamics during the transition to parenthood, as well as providing a foundation for designing more effective interventions.Masa transisi menjadi orang tua merupakan fase kritis dalam kehidupan pernikahan yang dapat berdampak pada berbagai aspek dalam pernikahan. Perubahan peran, peningkatan tanggung jawab, serta tekanan emosional dan fisik pasca kelahiran anak dapat memengaruhi dinamika hubungan pasangan yang pada akhirnya juga dapat memengaruhi kepuasan pernikahan. Meskipun topik kepuasan pernikahan telah banyak dikaji, masih terbatas penelitian yang secara sistematis mengeksplorasi faktor-faktor yang memengaruhinya dalam konteks transisi menjadi orang tua. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi berbagai faktor yang berkontribusi terhadap kepuasan pernikahan selama masa transisi tersebut. Tinjauan literatur menggunakan pendekatan Systematic Literature Review (SLR) berdasarkan pedoman PRISMA, dengan pencarian artikel pada lima database utama, yaitu APA PsycArticles, PubMed, Scopus, Sage Journals, dan Taylor & Francis. Dari 20 artikel yang memenuhi kriteria inklusi, ditemukan bahwa kepuasan pernikahan dipengaruhi oleh faktor individual (attachment, self-compassion, self-regulation, emotion, mindfulness, psychological distress, dan own body satisfaction) dan faktor relasional (persepsi terhadap pasangan, komunikasi, hubungan interpersonal, penyelesaian konflik, seksual, dan kesiapan menjadi orang tua). Secara keseluruhan, kepuasan pernikahan selama transisi menjadi orang tua muncul dari interaksi kompleks antara faktor-faktor tersebut. Hasil ini diharapkan dapat menjadi acuan bagi konselor dan psikolog dalam memahami kompleksitas dinamika pernikahan pada masa transisi menjadi orang tua, sekaligus menjadi dasar untuk merancang intervensi yang lebih efektif.